Quantitative receptor model for responses that are left- or right-shifted versus occupancy (are more or less concentration sensitive): the SABRE approach - Buchwald, Peter (Frontiers in Pharmacology, 2023)
Simple one-to three-parameter models routinely used to fit typical dose-response curves and calculate EC 50 values using the Hill or Clark equation cannot provide the full picture connecting measured response to receptor occupancy, which can be quite complex due to the interplay between partial agonism and (pathway-dependent) signal amplification. The recently introduced SABRE quantitative receptor model is the first one that explicitly includes a parameter for signal amplification (γ) in addition to those for binding affinity (K d ), receptor-activation efficacy (ε), constitutive activity (ε R0 ), and steepness of response (Hill slope, n). It can provide a unified framework to fit complex cases, where fractional response and occupancy do not match, as well as simple ones, where parameters constrained to specific values can be used (e.g., ε R0 =0, γ=1, or n=1). Here, it is shown for the first time that SABRE can fit not only typical cases where response curves are leftshifted compared to occupancy (κ=K d /EC 50 >1) due to signal amplification (γ>1), but also less common ones where they are right-shifted (i.e., less concentration-sensitive; κ=K d /EC 50 <1) by modeling them as apparent signal attenuation/loss (γ<1). Illustrations are provided with μ-opioid receptor (MOPr) data from three different experiments with one left-and one right-shifted response (G protein activation and β-arrestin2 recruitment, respectively; EC 50,Gprt